Impact of Maternal Obesity on Pregnancy Outcome - Sinha, K; Pandey, S; Das, C R (Journal of Nepalgunj Medical College, 2018)
Background: Maternal obesity increases the risk of complications of pregnancy, labor, and neonate. It has been associated with gestational hypertension, eclampsia, pre-eclampsia, gestational diabetes, cesarean delivery, instrumental delivery, abortion, postpartum haemorrhage, puerperal infection and perinatal outcome like macrosomia, still birth and congenital anomaly, birth asphyxia.Aims: To evaluate the effect of maternal obesity on pregnancy outcome.Methods: The hospital based observational study conducted in the department of Obstetrics & Gynaecology at Nepalgunj Medical College Teaching Hospital Kohalpur between September 2015 to August 2016.Results: Mean age of participant's in the study group was 28 ± 5.77 and youngest participant's age was 19 yrs and oldest participant was 45 yrs. Among the fifty five ladies, 10 were grand multigravida, 30 were multi and 15 were primigravida. 63.6% delivered by cesarean section,1.8% delivered by forceps with episiotomy, 9.1% delivered by svd, 20% by svd with episiotomy and 5.5% by vacuum with episiotomy. Ten participants (18.18%) had hypertensive disorder during pregnancy. The mean BMI was 33±2.4. Under obese class 1 and class 2 were 49.1% and 50.9% respectively. Among the study population 56.36% had complications. Mean BMI was 33 minimum being 30 and maximum was 39.81. Regarding body weight maximum was 90 kgs. and 2 2. minimum was 68 kgs and mean weight being 78 kgs. Regarding maternal height maximum was 2.7 m , minimum was 2.01 m and 2 mean was 2.33 m . Total 7 newborn (13%) were macrosomic. Among 55 cases 27 fall under obesity class 1, 11 ladies with complication and among 28 ladies under obesity class 2, 22 had complications.Conclusion: The obesity has adverse effects on pregnancy outcome both for mother and the foetus.JNGMC, Vol. 14 No. 2 December 2016, Page: 18-22